Risk factors of development of Post Mastectomy Pain Syndrome (PMPS) and its impact on the psychological symptoms in patient with PMPS / Chua Kah Yee - Evarina , Amiron (2024)
Background: Post-mastectomy pain syndrome (PMPS) is a common complication following breast cancer surgery, characterized by persistent neuropathic pain. Objective: To determine the prevalence of PMPS, identify its risk factors, and assess its impact on psychological symptoms in affected patients. Method: The study successfully recruited 202 patients with complete medical records. Inclusion criteria comprised women diagnosed with breast cancer who underwent surgery at PPUM in 2022, while exclusion criteria included patients who declined study consent, were unreachable, or faced communication barriers. These patients were assessed for PMPS according to the IASP definition. For those with PMPS, pain characteristics were documented, pain intensity was measured using the numeric rating scale (NRS), and psychological symptoms were evaluated using the Hospital Depression and Anxiety Score (HADS). Univariate and multivariate logistic regression analyses were conducted to identify PMPS risk factors. Results: Among the 202 patients, 14 (7%) reported PMPS, with pain predominantly described as mild or moderate intensity localized in the ipsilateral breast or chest wall, often characterized as throbbing. Risk factors for PMPS encompassed younger age, increased weight, high BMI, neoadjuvant chemotherapy, sentinel lymph node biopsy (SLNB), and axillary lymph node dissection (ALND), all exhibit p-values < 0.05. Among patients with PMPS, two experienced mild depression, one experienced mild anxiety, and one experienced moderate anxiety. Conclusion: PMPS significantly impacts patient morbidity, psychological well-being, and quality of life. Identifying potential risk factors for PMPS is crucial for implementing early multimodal and multidisciplinary approaches to prevent or alleviate this condition.